Chapter 18. Robotics in Pharmaceutical Manufacturing and Computational Fluid Dynamics (Computer Aided Drug Development, 2024)
AuthorDr. Naga Aparna TAssociate Professor, Department of Pharmaceutics, G. Pulla Reddy College of Pharmacy, Mehdipatnam, Hyderabad, Telangana, IndiaAbstractModern pharmaceutical manufacturing has been transformed through the integration of robotics and Computational Fluid Dynamics (CFD), creating a sophisticated technological framework for process optimization and control. Advanced robotic systems perform complex manufacturing tasks with unprecedented precision, while CFD provides detailed insights into fluid dynamics through computer-based simulation. Collaborative robots work alongside humans, enhancing productivity and safety, while CFD's mathematical models analyze and predict fluid flow patterns, heat transfer, and associated phenomena. Automated guided vehicles optimize material flow as CFD applications span mixing operations, spray drying, tablet coating, and bioreactor design. Industry 4.0 principles connect these systems with manufacturing execution systems, creating a comprehensive digital manufacturing environment. The combination of robotics and CFD significantly reduces manufacturing costs, improves product consistency, and accelerates process development while ensuring regulatory compliance and workplace safety.Keywords: Collaborative Robots; Computational Fluid Dynamics; Process Automation; Numerical Simulation; Heat Transfer; Industry 4.0View PDF